Determination of leucomalachite green, leucocrystal violet and their chromic forms using excitation–emission matrix fluorescence coupled with second-order calibration after dispersive liquid–liquid microextraction. (15th October 2015) - Ju, Saiqin; Deng, Jian; Cheng, Jianlin; Xiao, Ni; Huang, Kaihui; Hu, Canhui; Zhao, Haiqing; Xie, Jin; Zhan, Xiaozhu
Highlights: A spectrofluorimetric method for trace determination of LMG, LCV, MG and CV. Sodium borohydride was used to reduce MG and CV to fluorescent LMG and LCV. DLLME process for the preconcentration of the interested analytes. The overlapping spectra were successfully resolved by PARAFAC and ATLD. The developed method outperformed many of the reported techniques. Abstract: A novel spectrofluorimetric method has been developed for the simultaneous determination of leucomalachite green (LMG), leucocrystal violet (LCV), malachite green (MG) and crystal violet (CV) by combining the sensitivity of molecular fluorescence and the selectivity of the second-order calibration. Residues of LMG, LCV, MG and CV were simultaneously extracted from fish and shrimp muscle with acetonitrile. The non-fluorescent CV and MG were then reduced to the corresponding fluorescent LMG and LCV by reacting with sodium borohydride. After preconcentration with dispersive liquid–liquid microextraction technique, the extracts were analyzed by using excitation–emission matrix fluorescence coupled with second-order calibration methods based on parallel factor analysis (PARAFAC) and alternating trilinear decomposition (ATLD) algorithms. The limits of detection obtained were 2.21–2.65 ng g −1 by PARAFAC and 2.30–2.86 ng g −1 by ATLD, respectively. The developed method was successfully applied to simultaneous determination of the four analytes in grass carp and shrimp samples with recoveries of 90.53–103.03% for PARAFAC and 90.40–102.75% for ATLD. The accuracy of this novel method was also verified by high performance liquid chromatography.